AD, Volume 14, n° 1, 1989 - Full Issue - journal system (Africa Development, 1989)
Table of Contents Une Nouvelle Expérience d'Integration Régionale en Afrique: La Zone d'Echanges Préférentiels (ZEP) des Etats de l'Afrique de l'Est et de l'Afrique Australe Guy Martin .............................. 5 Alternatives Approaches to Economic Integration in Africa J. K. Thisen ............................. 19 Regional Economy and Foreign Capital in economic Integration in Africa: Reflections on ECOWAS Obuah Emmanuel Ezi .................. 61 Book Reviews Max Assimeng, Saints and Social Structures Kwame A. Ninsin .................. 125 Kjell J. Havnevik, The IMF and World Bank in Africa: Conditionality, Impact and Alternatives Akwasi Aidoo ...................... 127 M. Lakehal, A l'Ombre de l'Occident Naceur Bourenane .................... 130 Garba Joe, Diplomatic Soldiering : Nigerian Foreign Policy , 1975-1979 Andrew I. Owona .......................... 131 Publications Received ...................... 135 Index to Africa Development - vol.XIII, 1988 ...........138